Bridging the HIV-syphilis testing gap: dual testing among men who have sex with men living in China. (20th August 2018) - Ong, Jason J; Liao, Meizhen; Lee, Amy; Fu, Hongyun; Pan, Stephen W; Tang, Weiming; Wei, Chongyi; Dan, Wu; Yang, Bin; Yang, Ligang; Wang, Cheng; Tucker, Joseph D
Abstract : Objectives: The WHO recommends dual testing for HIV and syphilis among key populations, including men who have sex with men (MSM). We assessed the proportion of men who had dual tested and reasons for not dual testing. Methods: In 2017, an online survey of MSM was conducted in eight cities from two provinces in China. Data on sociodemographics and sexual behaviours were collected. Descriptive analysis was used to examine the experience of dual testing. Multivariable logistic regression identified characteristics associated with men who had dual tested. Results: Among 802 men who had ever tested for HIV, 297 dual tested (37%, 95% CI 34 to 40). Men dual tested in a variety of settings: public hospital (35%), voluntary counselling and testing sites (28%), self-testing at home (18%), community-based organisation (8%), community health centre (7%), other (3%) or private hospital (1%). Greater odds for dual testing was found in men who had disclosed their sexuality to a healthcare provider (adjusted OR (AOR) 1.81, 95% CI 1.27 to 2.59, p=0.001), and who had substantial (AOR 2.71, 95% CI 1.67 to 4.41, p<0.001) or moderate community engagement in sexual health (AOR 2.30, 95% CI 1.49 to 3.57, p<0.001), compared with those with no community engagement. The most common reasons for not dual testing were no knowledge that they could be dual tested (34%), did not ask the doctor to be dual tested (25%) and did not believe they were at risk for syphilis (19%). Conclusions: Chinese MSM are dual testing through a variety of test sites, including home self-testing. However, the overall dual testing rate remains low despite recent efforts to integrate HIV and syphilis testing.